Lunar and Planetary Webcam User's Guide - Mobberley, Martin (The Patrick Moore Practical Astronomy Series, 2006)
Inexpensive webcams are revolutionizing imaging in amateur astronomy by providing an affordable alternative to cooled-chip astronomical CCD cameras, for photographing the brighter astronomical objects. Webcams - costing only a few tens of dollars - are capable of more advanced high resolution work than "normal" digital cameras because their rapid image download speed can freeze fine planetary details, even through the Earth's turbulent atmosphere. Also, their simple construction makes it easy to remove the lens, allowing them to be used at high power at the projected focus of an astronomical telescope. Webcams also connect direct to a PC, so that software can be used to "stack" multiple images, providing a stunning increase in image quality. In the Lunar and Planetary Webcam User's Guide Martin Mobberley de-mystifies the jargon of webcams and computer processing, and provides detailed hints and tips for imaging the Sun, Moon and planets with a webcam. He looks at each observing target separately, describing and explaining all specialised techniques in context. Glance through the images in this book to see just how much you can - easily - achieve by using a webcam with your telescope!